The Role of Folk Pedagogy in Child Raising and in Maintaining National Identity in the Latvian Villages of Siberia - Antiņa, Ināra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
A large number of Latvia’s inhabitants have left the country recently due to a variety of reasons. There have been several waves of emigration in Latvia’s history. Generations of Latvians live in different parts of the world. Many have become assimilated in their country of destination, but there are communities of Latvians that have maintained their national and cultural identity, as well as traditions for well over a century. The goal of this study is to identify the set of skills, situations and character education – known as folk pedagogy - that are central to the retention of the Latvian idenity in the Latvian villages of Augšbebi (Bobrovka) and Kurzemes Ozolaine (Kurļanddubovka) in the Russian region of Omsk in Siberia.An understanding of folk education is particularly relevant in this period of regional mobility, when many people are leaving Latvia, finding themselves new places of residence and trying to maintain their ethnic identity.